PENGARUH KEDISIPLINAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN (Studi Pada KSP Tunas Artha Mandiri Nganjuk) - Sulasari, Ayu (Fakultas Ekonomi, UIN Maliki Malang, 2013)
The research has been done at KSP Tunas Artha Mandiri in Nganjuk. It examines the influence of disciplines on the employee performance. The objective of this research is, that the employee don’t have discipline in the works so that influence the employee performance. The fisrt result from this reseach show that discipline and properous, discipline and punishment, certain on discipline done, discipline support the purpose, participations of the discipline, and the example from leader as key a discipline were influencing the work spirit or performance. The second result show that the dominant factor influence work spirit or performace employee is certained on the discipline done. So we have the conclution that this conditions suitable with actual conditions in KSP Tunas Artha Mandiri – NGANJUK. Although prosperously has a good condition but work spirit or performance employee don’t maximal. This is make H2 refused, but if certain on disipline done built up make work spirit or performance employee good more.